THE ROLE OF THE KATINGAN REGENCY GOVERNMENT TOWARDS ILLEGAL GOLD MINERS IN HAMPALIT VILLAGE - Novi Lidiyasari; Surya Sukti; Sabarudin Ahmad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The rise of Unlicensed Gold Mining (PETI) activities in Hampalit Village, Katingan Regency, has created an environmental crisis and complex socio-economic dilemmas. Regional policies such as Katingan Regent Regulation No. 44 of 2023 have not been able to effectively overcome this problem, mainly because of the community's dependence on mining as the main livelihood and the limited regional authority after the enactment of the Minerba Law. Using empirical and sociolegal legal approaches, this study examines the dynamics of the policy and its implementation through literature studies, legal documentation, and in-depth interviews with the Environmental Agency, community leaders, law enforcement officials, and local miners. The results show that despite efforts to curb mining and environmental rehabilitation programs, weak synergies between levels of government and the lack of viable economic alternatives are the main obstacles. A sustainable strategy that includes the establishment of a People's Mining Area (WPR), local economic empowerment, and more adaptive regulatory coordination between local, provincial, and central governments is needed to create a fair, legal, and environmentally friendly solution to PETI practices in this region.